The effect of venting process on the progress of a vented deflagration. (2nd April 2019) - Schiavetti, M.; Pini, T.; Carcassi, M.
Abstract: Vented deflagrations are one of the most challenging phenomenon to be replicated numerically in order to predict its resulting pressure time history. As a matter of fact a number of different phenomena can contribute to modify the burning velocity of a gas mixture undergoing a deflagration, especially when the flame velocity is considerably lower than the speed of sound. In these conditions acceleration generated by both the flow field induced by the expanding flame and from discontinuities, as the vent opening and the venting of the combustion products, affect the burning velocity and the burning behavior of the flame. In particular the phenomena affecting the pressure time history of a deflagration after the flame front reaches the vent area, such as flame acoustic interaction and local pressure peaks, seem to be closely related to a change in the burning behavior induced by the venting process. Flame acoustic interaction and local pressure peaks arise as a consequence of the change in the burning behavior of the flame. This paper discuss the analysis of the video recording of the flame front produced during the TP experimental campaign, performed by UNIPI in the project HySEA, to describe qualitatively the contribution of the generated flow field in a vented deflagration and its influence in the peaks of the pressure-time history. Highlights: Experimental tests of hydrogen vented deflagration in a 1.14 m 3 test facility. Analysis of the venting process with focus on vent burst and flame reaching the vent. Photo analysis of the effects generated by the perturbations on the flame front. Interaction of the acceleration generated during the vent burst with the flame bubble. Description of the behavior of the flame front after it reaches the vent area.